Performing images opera in Chinese visual culture - Zeitlin, Judith T. 1958-; Li, Yuhang; Hay, Jonathan 1956-; David and Alfred Smart Museum of Art. (Chicago Smart Museum of Art, The University of Chicago, 2014)
"Writing in the early nineteenth century, the French traveler and cleric Abbe Huc exclaimed: "There is, perhaps, not a people in the world who carry so far their taste and passion for theatrical entertainments as the Chinese." Although the spectacle of this theater is well known, with its colorful costumes, props, and face painting, the extent to which opera was favored in Chinese pictorial and decorative motifs across the full spectrum of visual media-from courtly scroll paintings, popular New Year prints, illustrated woodblock books, and painted fans to carved utensils, ceramics, textiles, and dioramas-will surprise many. As the first comprehensive publication in English on the subject, Performing Images is not only a major interdisciplinary contribution to existing scholarship-featuring eight new essays by experts in the fields of traditional and modern Chinese literature, art, material culture, and history-but also a visual spectacle in its own right. A companion volume to the exhibition of the same name at the Smart Museum of Art, Performing Images contains more than one hundred color reproductions and over eighty illustrated catalogue entries. Together, text and image offer new insight into traditional Chinese culture, visual arts, and theater, and reveal how Chinese visual and performing traditions were aesthetically, ritually, and commercially intertwined"-- Provided by publisher.
Introduction: Toward a Visual Culture of Chinese Opera / Judith T. Zeitlin -- World-Making in Performance and Painting: An Intertwined History / Jonathan Hay -- Opera Imagery in the Village / David Johnson -- Images of Opera Characters Related to the Qing Court / Mei Mei Rado -- Representing Theatricality on Textiles / Yuhang Li -- Operatic Images in Popular New Year Prints / Bo Songnian -- The Iconographic Variations of Two Scenes from Romance of the Western Chamber / Ni Yibin -- Inspired by the Opera: Reimagining Traditional Opera in Contemporary Chinese Photography and Video / Wu Hung.
"Published on the occasion of the exhibition Performing Images: Opera in Chinese Visual Culture, co-curated by Judith T. Zeitlin and Yuhang Li and organized by the Smart Museum of Art, University of Chicago."
Includes bibliographical references.
Keywords: Opera in art -- Exhibitions; Art, Chinese -- Exhibitions; Operas, Chinese -- Exhibitions; Art and society -- China -- Exhibitions